The coproduction of a multilevel personal narrative intervention for people with aphasia in a community communication support group—A pilot study - Charalambous, Marina; Symeou, Rafaella Tereza; Theodorou, Elena; Kambanaros, Maria (Frontiers in Stroke, 2024)
Introduction: People with aphasia (PWA) face challenges in sharing personal stories due to communication difficulties. Discourse treatment in aphasia focusing on personal narrative macrostructure has yet to receive the attention this warrants of researchers and clinicians. Emerging person-centered approaches involve coproduction and codesign with PWA for meaningful discourse treatments. Few studies explore discourse treatment's impact on functional communication. This pilot study aims to explore whether the use of the coproduction approach in the development of a multilevel personal narrative intervention at the group level increased the production of macrostructure elements in trained and untrained narrative discourse contexts, improved aphasia severity and functional communication skills, and advanced quality of life of the participants with aphasia.Methods: An ABA design was followed featuring a pre-treatment baseline assessment phase, a treatment phase, and a post-treatment assessment phase immediately after treatment was completed.Three people with chronic stroke-induced aphasia, three communication partners, and a moderator took part in the study. All participants were members of a university-led community aphasia communication group. The research protocol consisted of eleven, two-hour, weekly sessions over an 11-week block.Nine treatment sessions were carried out following codesign and coproduction methods that focused on participants with aphasia producing words, sentences, and total communication strategies to express macrostructure elements in their personal stories. Assessment measures were collected at baseline and post-treatment to evaluate improvements in trained and untrained narrative abilities, aphasia severity, functional communication, and the impact of aphasia on quality of life.Results: Multilevel personal narrative therapy improved the narrative skills of the participants with aphasia at the macrostructural level of narrative discourse. Improvements were also observed in functional communication and quality of life post-treatment.Discussion: The involvement of participants with aphasia in the codesign and coproduction of the treatment content for the group intervention facilitated improvement in narrative skills, functional communication, and overall quality of life with aphasia. It is recommended that researchers and clinicians consider using content from the personal narratives of clients with aphasia to build discourse treatment and adopt codesign and coproduction approaches, when designing interventions for people with chronic aphasia, to improve communication outcomes in everyday life.